Synthesis on growth patterns and mechanisms in Mediterranean-alpine shrubs - Albrecht, Eike Corina; Dobbert, Svenja; Pape, Roland; Löffler, Jörg (ERDKUNDE, 2025)
In the context of open questions on the adaptability of alpine ecosystems to future global warming, we studied three Mediterranean-alpine shrub species using dendrometers. Here, we synthesize our research approach and the main findings from three previously published articles. Under climate change, cold-adapted Mediterranean-alpine shrubs might become exposed to severe summer droughts and milder winters. However, neither the physiological strategies for coping with winter cold and summer drought nor the adaptability of these shrubs to climatic variability are yet fully understood. Here, we used Cytisus galianoi as a target species, which was abundant at manifold sites across the Sierra Nevada. We compared the species’ adaptation mechanisms to frost and drought with those of Astragalus granatensis, a shrub species co-occurring at exposed ridges, and those of Genista versicolor, a shrub species co-occurring at snow-covered slopes. Previous dendroecological studies on shrubs commonly used anatomical ring-width-based approaches. In contrast, we aimed at understanding stem diameter changes, water-related stem expansion and contraction, and physiological strategies for coping with winter cold and summer drought by combining long-term, high-resolution dendrometer measurements with soil temperature and soil moisture data recorded directly at the growing sites. From our findings, we deduced the species’ strategies to cope with the climatic constraints. We show that the green-stemmed species C. galianoi is frost and drought tolerant, likely profiting from cold and snow-free winters by mobilizing assimilates from winter photosynthesis for major spring growth. C. galianoi showed severe summer stem contractions, and revealed strong water-related stem diameter increase due to rehydration in autumn, while growth rates were minor. Using this combined winter cold and summer drought tolerance strategies, C. galianoi showed great competitive advantages and performed best at all alpine sites due to its high growth plasticity. In contrast, we show that G. versicolor uses a winter-cold escape and summer-drought avoidance strategy and exhibits a far narrower ecological niche, which is restricted to snow-covered alpine slopes. The observed pattern of stem diameter change in A. granatensis suggests frost avoidance by osmoregulation and drought avoidance by maintaining high tissue water potential throughout summer, as indicated by constantly expanding stems. This makes it competitive at the highest, most exposed ridge sites where harsh conditions prevail during winter. Here, we synthesize how we derived the different growth strategies and address a) the overall growth performance in C. galianoi over its distributional range across the Sierra Nevada, b) the advantages and disadvantages of growth strategies in a green-stemmed and a seasonal dimorphic species, and c) the growth differences in comparison of two green-stemmed species at shared sites.